Effectiveness of the Supervisory Board of Notaries (Mpdn) Supervisory Board Supervisory Board (Mpdn) on Violations of the Code of Ethics for the Notaries Office in Pandeglang Regency - Haq, Fazal; Widayati, Widayati (Jurnal Konstatering, 2025)
Supervision by the Regional Notary Supervisory Council (MPDN) is not only the implementation of the duties and positions of Notaries to comply with the provisions of the Notary Law, but also supervision of the behavior of Notaries that can harm the dignity of the Notary's position. This study aims to determine and analyze the Effectiveness of MPDN Supervision of Violations of the Notary Code of Ethics in Pandeglang Regency; and to determine and analyze the obstacles and solutions in MPDN Supervision of the implementation of the duties and positions of Notaries in Pandeglang Regency. The approach method used in this study is empirical legal research using primary data as the main data and secondary data as library data. This study uses a qualitative analysis approach. Based on the research results, it can be seen that MPDN is still not effective in supervising Notaries in Pendeglang Regency in carrying out their duties and authorities. In its implementation, related to the authority of MPDN to receive reports, MPDN then holds a hearing to examine any alleged violations of the implementation of the notary's position, but MPDN is not given the authority to impose any sanctions. MPDN is only authorized to report the results of the hearing and examination to the Notary Regional Supervisory Board (MPWN) with a copy to the reporting party, the notary concerned, the Central Supervisory Board, and the notary organization.Keywords: Notary; Position; Supervisory; Violations